Localized Multilayer Shielding of an Electron Beam Irradiation Station for FLASH Radiotherapy Experiments - Kanlayaporn Kongmali; Pittaya Apiwattanakul; Phanthip Jaikeaw; Sakhorn Rimjaem (Particles)
FLASH radiotherapy (FLASH-RT) is a cancer treatment delivering high-dose radiation within microseconds, reducing side-effects on healthy tissues. Implementing this technology at the PBP-CMU Electron Linac Laboratory poses challenges in ensuring radiation safety within a partially underground hall with thin walls and ceiling structures. This study develops a localized shielding design for electron beams (6–25 MeV) using the GEANT4 release 11.2.2 Monte Carlo simulation toolkit. A multilayer system of lead, iron, polyethylene, and concrete effectively attenuates X-rays, gamma-rays, and neutrons, achieving dose levels below 1 mSv/year for public areas and within 20 mSv/year for controlled areas, meeting international standards. The B-factor analysis highlights efficient low-energy gamma attenuation and thicker shielding requirements for high-energy rays. The design minimizes radiation leakage, ensuring safe operation for FLASH-RT while safeguarding personnel and the environment. Future work includes constructing and validating the system, with methodologies applicable to other electron beam facilities.